Sustainable Construction Using PET Bricks - Moya, Juan Carlos (2019)
This research project demonstrates the problems in the Metropolitan District of Quito, due to the high consumption by the society of plastic materials including polyethylene terephthalate (PET) which does not have an appropriate final destination. In the first place, the project provides favorable factors for sustainable construction, because it tries to mitigate the problem of pollution and the reduction of the use of traditional masonry. The objective is to provide society with construction alternatives through the recycling of high consumption materials to conserve the environment, a way of mitigation is the reuse of plastic bottles of any capacity as building elements of masonry. This new construction must comply with parameters that provide security to its occupants, for this the research will determine through tests in masonry specimens the design bases for the construction with recycled elements, verifying the results with the norms in force in the Country.